Antioxidant activity of Phaleria macrocarpa (Mahkota Dewa) fruits / Ahmad Farid bin Asmail @ Ismail - Asmail @ Ismail, Ahmad Farid (2014)
The study was conducted to determine the antioxidant activity of fruit and seed parts of Phaleria macrocarpa in hexane, chloroform, methanol and water extracts. The antioxidant activity were evaluated using in-vitro bioassay system namely 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, Ferric Reducing Antioxidant Power (FRAP) Assay and Metal Chelating Assay. In the DPPH assay, water extract of Phaleria macrocarpa fruit had the highest antioxidant activity with IC50 of 1.56 ug/ml while in Phaleria macrocarpa seed, chloroform extract showed good free radical scavenging activity with IC50 of 1.83 ug/ml when compared with standard ascorbic acid (IC50 = 1.25 ug/ml). For isolated compounds of Phaleria macrocarpa fruit and seed, compounds isolated from chloroform and water extracts had showed the highest antioxidant activity, respectively. Meanwhile, antioxidant activity of fruit and seed of Phaleria macrocarpa extracts measured using FRAP assay showed that methanol extract had the highest antioxidant capacity (absorbance at 0.339 nm and 0.13 nm, respectively) at concentration of 400 ug/ml when compared with standard of Butylated hydroxyanisole (BHA) with absorbance 0.632 nm at 400 ug/ml. For isolated compounds of Phaleria macrocarpa fruit and seed, methanol extracts again showed highest measurement for antioxidant activity. In the metal chelating assay, chloroform extract of Phaleria macrocarpa fruit had the most chelating activity of all extracts with 30% at concentration of 400 ug/ml, whereas in Phaleria macrocarpa seed, methanol extract showed the highest chelating activity of 32% at concentration of 400 ug/ml when compared to EDTA which was 90% at 400 ug/ml. For isolated compounds of Phaleria macrocarpa fruit and seed, water and methanol extracts had showed highest chelating activity, respectively. The chemical compounds found in Phaleria macrocarpa fruit extract were mangiferin, mangiferin isomers, quinic acid, lignan and benzophenone derivatives while in Phaleria macrocarpa seed extract was mangiferin from LCMS analyses. GCMS analyses had successfully identified squalene, farnesene, diethyl phthalate, tricosane and sitosterol as key chemical compounds found in Phaleria macrocarpa fruit extract, while the key chemical compounds found in Phaleria macrocarpa seed extract were squalene, dodecanoic acid, diethyl phthalate, tetradecanoic acid, methyl ester and n-hexanedecanoic acid. Total phenolic contents (TPC) of Phaleria macrocarpa fruit extracts estimated as gallic acid equivalent (GAE) was found highest in chloroform extracts at 7.9±0.01 mg GAE/g dry weight while for Phaleria macrocarpa seed, hexane extracts had showed the highest total phenolic content at 8.21±0.01 mg GAE/g dry weight. Meanwhile, Total flavonoid contents (TFC) of Phaleria macrocarpa fruit extracts estimated as quarcetin equivalent (QE) was found highest in methanol extracts at 2.32±0.01 mg QE/g dry weight whereas for Phaleria macrocarpa seed, hexane extracts recorded the highest total flavonoid content at 2.38±0.01 mg QE/g dry weight. All of the Phaleria macrocarpa fruit and seed extracts were put throughout preliminary brine shrimp toxicity bioassay. All Phaleria macrocarpa fruit and seed extracts tested were found to be non toxic as the high extracts concentration of 10 ug/ml to 1000 ug/ml was needed to cause more than 50% mortality in the Artemia salina nauplii. In conclusion, fruit and seed of Phaleria macrocarpa show good antioxidant activity. This activity might be due to the presence of phenolics and flavonoid compounds with various appreciable amounts. Thus, these results suggest that Phaleria macrocarpa can be used as source of natural antioxidant and supplement in nutritional and pharmaceutical industry.